THE EFFECT OF SERVICE QUALITY ON CUSTOMER LOYALTY: CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE AT HELLEN HEALTH AND BEAUTY SALON, KARIMUNTING VILLAGE - Yulan Plasza; Ananda Archie (Universitas KH. Abdul Chalim Mojokerto, 2026)
The beauty industry in Indonesia has shown rapid development along with the increasing public awareness of personal care and appearance, which drives the growth of businesses and intensifies competition in the beauty services sector. This condition is accompanied by rising customer demands for optimal service quality, but there are still issues in retaining customer loyalty, which is influenced by the level of satisfaction experienced. This study aims to analyze the effect of service quality on customer loyalty: customer satisfaction as an intervening variable at Hellen Health and Beauty Salon, Karimunting Village. This study uses a quantitative approach with a causal associative design. The population of the study is all salon customers, with a sample of 150 respondents determined through purposive sampling. Primary data were collected through questionnaires, observation, and interviews, while secondary data were obtained from publications related to the development of the beauty industry. Data analysis was performed using SEM-PLS with SmartPLS by evaluating the outer model (convergent validity, discriminant validity, AVE, and reliability) and the inner model (R-square, F-square, and hypothesis testing through bootstrapping). The results show that all constructs meet the validity and reliability criteria. The model has moderate explanatory power with a customer satisfaction R² value of 0.538 and a customer loyalty R² value of 0.583. Service quality significantly positively affects both customer satisfaction and customer loyalty, and customer satisfaction significantly positively affects customer loyalty. Customer satisfaction also acts as a partial mediator in the relationship between service quality and customer loyalty.